PENGARUH PERSEPSI PROFESI GURU DAN DUKUNGAN KELUARGA TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS MUHAMMADIYAH PURWOREJO - Handayani, Dewi Widiya; Setiaji, Cahyo Apri; Rinawati, Anita (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research aims to determine whether there is a positive and significant influence between perceptions of the teaching profession and family support, both individually and as a stimulant, on the interest in becoming a teacher among all Economic Education students at FKIP Muhammadiyah University, Purworejo. The total population of 94 students was taken as a sample of 77 students. Data collection uses a questionnaire method that has been tested for validity and reliability. Data analysis techniques use descriptive analysis, inferential analysis, and classical assumption tests. The results of descriptive analysis show that the perception of the teaching profession is in the good category (51.94%), family support is in the good category (50.64%) and interest in becoming a teacher is in the very good category (84.41%). Based on the results of inferential analysis, it shows that perceptions of the teaching profession have a positive and significant effect on interest in becoming a teacher by 84.27% r = 0.918, t_count= 19.964, sig 0.000). The positive and significant influence between family support and interest in becoming a teacher is 81.72% (r) = 0.904, t_count= 18.156, sig 0.000. There is a positive and significant influence between perceptions of the teaching profession and simultaneous family support of 91.80% (R) = 0.958, F_(calculated) = 413.787 sig 0.000. Meanwhile, 8.20% is influenced by other variables not studied.